Innovative Integration: Exploring AI Art Platforms in Architectural Education for Mosque Facade Design - Afif Fajar Zakariya; Wiwik Dwi Susanti; Vijar Galax Putra Jagat Paryoko (Nurul Jadid University, 2023)
This research aims to investigate the effectiveness of implementing the mentoring model in Mosque facade design presents a unique challenge in the field of architecture due to their importance as the mosque's front-facing feature and their role in representing Islamic identity. In this study, an AI art platform was introduced as a tool to improve the creativity and design process for architecture students and professionals. The study investigated the platform's novel application in the context of architectural learning for mosque façade design. The research methodology was divided into three parts: a description of the platforms used, identification of common use cases in mosque architectural design, and query analysis using NLP methods in Midjourney AI art platform. According to the findings of the study, the AI art platform is a valuable tool for architectural learning, allowing students and professionals to generate diverse and innovative designconcepts. The Midjourney AI art platform has flaws such as difficulty recognizing architectural styles from specific regions.